Improving Knowledge And Learning Effective Communication In Patient Right Or Responsibilities At Hospital - Erlina Puspitaloka Mahadewi; Ade Heryana; Erwin Agustian Panigoro; Fori Yumita (International Journal of Educational Research & Social Sciences, 2021)
This present study is for achieve improving the process of education and information provided to patients, patients' families, and meeting the hospital accreditation standards, it is necessary to increase the ability and skills of hospital staff regarding effective verbal and non-verbal communication between doctors, nurses, patients, and patients' families in RSKJ Soeprapto Bengkulu Province Indonesia. Effective communication training that has been carried out before has not covered all staff who have been given education, where the requirements for health workers according to accreditation must take part in effective communication training and the rights obligations of family patients (HPK) and be certified. The purpose of this activity is to provide theoretical and practical knowledge to educators on how to establish effective communication between doctors, nurses, patients, and patients' families at RSKJ Soeprapto Bengkulu Jakarta. The method of implementing this activities are carried out in 2 (two) stages, the first stage is 80 people in July 2019 and the second stage is 58 people in June 2020, with 4 (four) sessions: 1) Pre-test by giving questionnaires to participants regarding effective communication, 2) Delivery of effective verbal and non-verbal communication materials, 3) Effective communication exercises and HPK (Role Plays and Simulations), and 4) Post-test by giving questionnaires to the audience according to the related training materials. The results of pre and post test data processing: healthcare management, workers, and educators of RSKJ Soeprapto Bengkulu understand and are expected to be able to provide health education and communicate well, precisely, clearly, completely, accurately, and can be understood by the recipient (communicant) in this case the patient and his family. In the future, it is expected hospital to reduce errors and improve health service improvements for the hospital management, patients, families and among hospital staff by knowing and having the same perception in the application of their rights and obligations in hospitals also the effective communication.